Validation of flank-to-flank measurements for predicting boar weight - Sulabo, R.C.; Quackenbush, J.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Allometric relationships, in which linear body dimensions are expressed as a function of body weight, are commonly used in growth studies. Previous work at Kansas State University showed a positive correlation between flank-to-flank measurement and sow body weight. Prediction equations were developed to estimate sow weight, but it is not known if the same equation will be valid in estimating body weight among other groups of pigs, such as boars. The objective of this study was to validate the use of flank-to-flank measurement in predicting boar weight, and to determine if the allometric equation for gestating sows can also be used for adult boars. A total of 100 adult working boars in a commercial A.I. stud were selected for this study. Flank-to-flank measurement and body weight were measured on each individual boar. Flank-to-flank measurement was positively correlated to boar body weight (R2 = 0.84, P<0.01). The fit of the model improved slightly (R2 = 0.86, P<0.01) when body weight was expressed as BW0.333. The boar equation was: BW0.333, kg = 0.0458 × flank-to-flank, cm + 1.1838. The comparison of residuals indicated that all three equations accurately predicted boar weight. The sow equation was also shown to be as accurate as the boar equations in estimating boar weight. Therefore, the sow allometric equation can be used as the final model to predict both sow and boar body weight.
Keywords: Boars; Flank-to-flank; Allometry; Prediction equations; Weight; Swine